2012
DOI: 10.1177/2048872612471212
|View full text |Cite|
|
Sign up to set email alerts
|

Serum extracellular vesicle protein levels are associated with acute coronary syndrome

Abstract: Aims: Biomarkers are essential in the early detection of acute coronary syndromes (ACS). Serum extracellular vesicles are small vesicles in the plasma containing protein and RNA and have been shown to be involved in ACS-related processes like apoptosis and coagulation. Therefore, we hypothesized that serum extracellular vesicle protein levels are associated with ACS. Methods and results: Three serum extracellular vesicle proteins potentially associated with ACS were identified with differential Q-proteomics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 48 publications
(43 reference statements)
0
56
0
Order By: Relevance
“…Spermatozoa were pelleted by centrifugation for 10 min at 1000 × g at 4°C. Seminal plasma or blood serum samples were stored at −80°C until purification of exosomes using ExoQuick (SBI) exosome precipitation reagent as previously described (de Hoog et al, 2013; Madison et al, 2014; Quackenbush et al, 2014; Rekker et al, 2013) or sucrose gradient differential ultracentrifugation (Madison et al, 2014). Supernatant (exosome depleted seminal plasma or blood serum) was discarded, the SE or BE exosome pellet was washed in PBS three times for 30 minutes at 4°C and 100,000 × g , resuspended in PBS vehicle, aliquoted, quantified by the Bradford method and stored at −80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Spermatozoa were pelleted by centrifugation for 10 min at 1000 × g at 4°C. Seminal plasma or blood serum samples were stored at −80°C until purification of exosomes using ExoQuick (SBI) exosome precipitation reagent as previously described (de Hoog et al, 2013; Madison et al, 2014; Quackenbush et al, 2014; Rekker et al, 2013) or sucrose gradient differential ultracentrifugation (Madison et al, 2014). Supernatant (exosome depleted seminal plasma or blood serum) was discarded, the SE or BE exosome pellet was washed in PBS three times for 30 minutes at 4°C and 100,000 × g , resuspended in PBS vehicle, aliquoted, quantified by the Bradford method and stored at −80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular vesicle protein levels, however, have only recently been described to carry information in the presence of ACS [15]. Following a proteomics discovery approach, we demonstrated in a chest pain cohort of 471 patients that pIgR, Cystatin C (CST3), C5a and total vesicle protein concentration are associated with the presence of ACS.…”
Section: Extracellular Vesicle Proteins For Diagnosis Of Acsmentioning
confidence: 99%
“…Although relatively unexplored due to technical challenges, vesicle proteins hold promise as mass spectrometry-based proteomic technology is rapidly emerging for identification and quantification of extremely low abundant proteins in a sample. This has already resulted in identification of vesicle proteins for the diagnosis of ACS [15] and prognosis of secondary cardiovascular events [17] in clinical cohorts. Isolation of plasma extracellular vesicle subpopulations is expected to lead to new and better cardiovascular vesicle protein biomarkers in a new sample set.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The relationship between plasma levels of C5a and cardiovascular risk has been investigated. In a study of 471 patients, serum C5a level was found significantly associated with acute coronary syndrome [32]. As well, elevated C5a level may be associated with increased cardiovascular risk (myocardial infarction, percutaneous coronary interventions, coronary artery bypass graft, carotid revascularization, stroke, and death) in patients with advanced atherosclerosis after a median follow-up of 22 months [20].…”
Section: Serum C5a Level and The Prognosis Of Atherosclerosismentioning
confidence: 99%